PENERAPAN DIVERSI TERHADAP ANAK SEBAGAI PELAKU TINDAKPIDANA PENCURIAN DENGAN KEKERASAN SECARA BERSAMA-SAMA - Suardi, Suardi; Surya, Yayan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2021)
This study provides examples of cases of children who are in conflict with the law for committing the crime of theft with violence which is carried out together whose case has been decided by the Medan High Court with its decision Number: 6/PID.SUS-ANAK/2017/PT.MDN. The formulation of the problem in the research is how to regulate the diversion of children as perpetrators of the crime of theft with violence? and how is the application of diversion in making decisions against children as perpetrators of violent theft in the Medan High Court Decision Number: 6/PID.SUSANAK/2017/PT.MDN?. The research method used by the author is a normative juridical method, which is a research that puts the law as a norm. The system of norms in question is about principles, rules of laws and regulations, court decisions, agreements and doctrines (teachings). Finally, based on the results of the study, the authors conclude that the application of diversion in making decisions against children as perpetrators of violent theft refers to Law Number 11 of 2012 concerning the Child Criminal Justice System and Law Number 35 of 2014 concerning Child Protection, especially those that regulate regarding the application of diversion to those who are in conflict with the law. In the Medan High Court Decision Number: 6/PID.SUSANAK/2017/PT.MDN, it turns out that the judge in his decision was guided by the law above so that the judge decided, even though the child (the defendant) was sentenced to prison for 10 (ten) months, does not need to be carried out by the Child, unless the Child has made peace in writing with the Child Victim or with the family of the Child Victim